Reading Literacy Competence Class XI - Imani, Nanda Aulia Luthfiana; Markhamah, M (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The aim of this research is to describe the reading literacy competency of class XI students at SMA Muhammadiyah 1 Surakarta as measured through the Minimum Competency Assessment (AKM), which is part of the National Assessment (AN) framework. This study focuses on understanding students’ cognitive abilities in the context of reading literacy. Methodology: This research uses a quantitative descriptive method. It was conducted at SMA Muhammadiyah 1 Surakarta in August 2024. The study involved a population of 30 class XI students. The data collection instrument used was a reading literacy competency test. Content validity was employed to ensure the accuracy of the instrument, while descriptive statistical analysis was used to analyze the data. Results: The results show that the reading literacy competency of students is generally high. A total of 83.3% of students were categorized as having very good and good reading literacy competencies, 13.3% were in the fair category, and 3.3% were in the low category. Applications/Originality/Value: This study provides an overview of students’ reading literacy competency levels using the AKM framework and highlights the effectiveness of AKM as a diagnostic tool for identifying students’ strengths and weaknesses in reading comprehension. The findings can serve as a reference for teachers and schools in planning targeted interventions to further improve literacy skills and in aligning classroom instruction with national competency standards.